Examining the universality of Brown and Levinsons Politeness model In the Arabic Gulf Context - alkhateeb, ibrahim (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Brown and Levinson proposed a model of politeness, aiming to put forward a universal model for acting politely. This model has been widely discussed and criticised in the fields of pragmatics and discourse analysis, with the main critique of the model of politeness being put forward by two Japanese researchers, Matsumoto and Ide, and by the Chinese researchers, Gu and Mao. They argue that Brown and Levinsons model is western biased and does not represent politeness norms found all over the world (Fukushima, 2000). In this paper, the universality of the model is discussed, referring to the Gulf Arabic culture and related literature about the way Arabic speakers perform politeness. The argument of the paper is in favour of the model and supports its universality. The paper starts with a review of the model and then presents the critique, followed by information on the Gulf Arabic way of doing politeness; this is to be tested by collecting and rating some Gulf Arabic speakers responses to a set of cases in a questionnaire.